The DOG 1 EXPRESSION IN DIFFERENTIAL DIAGNOSIS OF CHONDROBLASTOMAS AND ITS HISTOLOGICAL MIMICKERS - Nisar, Maryam; Mushtaq, Sajid; Hassan, Usman; Akhtar, Noreen; Azam, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: Chondroblastoma is rare benign cartilage forming tumor of bone predominantly in individuals less than 20 years of age. Recently immunohistochemical marker DOG 1 has been reported to help in the diagnosis in difficult cases where histological features overlap with other similar entities. Current study aims to assess the sensitivity and specificity of DOG 1 in the diagnosis of chondroblastomas.Study design: descriptive cross-sectional studyPlace and duration of study: The study was conducted from June 2015 to July 2017 in Department of Histopathology, Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan.Patients and methods: Total fifty-two patients were included in this study including 19 chondroblastomas, 21 giant cell tumors and 12 chondromyxoid fibromas. DOG 1 antibody was applied on all the casesResults: DOG 1 was positive in 100 % of cases of chondroblastomas. However, intensity and proportion of staining pattern was variable among them. 78% (n=15) cases showed diffuse moderate to strong expression while 22% (n=4) cases showed focal weak expression. Only 10% (n=2) cases of giant cell tumors and 33% (n=4) of chondromyxoid fibromas expressed focal weak expression for DOG 1.Conclusions: This study confirms 100 % expression of DOG 1 in cases of chondroblastomas but intensity and proportion of staining pattern was variable. Therefore DOG 1 may prove to be a useful immunohistochemical marker for diagnosis of chondroblastomas in the future in difficult cases in correlation with histological and radiological features.